Ritirarsi nella foresta: Gerontologia sociale e diritto hindu allo specchio attraverso i concetti di asrama e ṛṇatraya - Correndo, Chiara (De senectute, 2023)
The contribution aims at discussing the concept of aging in the framework of the Hindu legal tradition. The duties and obligations of elderly people are analysed through the theoretical lenses of the four stages of life and the theory of the «three debts». Arguing that the discipline of succession and maintenance impinge upon these normative premises, the contribution will introduce the reader to the concepts of «spiritual benefit» and reciprocity, as well as their ramifications and impact on the contemporary legal framework.